From Classrooms to Nature: Cultivating Children's Character Through Environmental Education - Nakiya, Mohamad; Kurniawan, Dede Trie; Abidin, Yunus (Balai Diklat Keagamaan Bandung, 2024)
This study investigates the urgency of environmental education in elementary schools to develop students' environmental awareness and character. Using a library research methodology, the analysis draws upon academic articles, policy documents, and reports to explore the theoretical underpinnings and practical implementations of environmental education. The study employs an interdisciplinary approach rooted in educational and environmental theories, such as Tilbury's sustainable education framework and Palmer-Cooper's multidimensional environmental education model. Findings highlight that integrating environmental education into the curriculum fosters cognitive, affective, and behavioral awareness among students, enabling them to connect their actions to broader ecological systems. Project-based learning (PjBL), extracurricular activities, and community collaborations emerge as effective methods for instilling environmental values and practical skills. For example, direct student involvement in waste segregation, tree planting, and energy conservation projects has proven to enhance environmental responsibility and empathy. Furthermore, deficiencies in national policies and infrastructure are identified as barriers to effective environmental education. The study concludes that environmental education at the elementary level is crucial for developing a generation committed to sustainable practices. Recommendations include incorporating environmental education across curricula, training teachers in innovative methods, and enhancing school-community partnerships. These measures aim to transform environmental education into a cultural cornerstone, equipping students with the knowledge, skills, and character to address global environmental challenges effectively. Keywords: Environmental Education; Character Development; Elementary School; Sustainability; Project-Based Learning